Environmental Contamination of Contact Precaution and Non-Contact Precaution Patient Rooms in Six Acute Care Facilities. (29th January 2021) - Tanner, Windy D; Leecaster, Molly K; Zhang, Yue; Stratford, Kristina M; Mayer, Jeanmarie; Visnovsky, Lindsay D; Alhmidi, Heba; Cadnum, Jennifer L; Jencson, Annette L; Koganti, Sreelatha; Bennett, Christina P; Donskey, Curtis J; et al.
Abstract: Background: Environmental contamination is an important source of hospital multidrug-resistant organism (MDRO) transmission. Factors such as patient MDRO contact precautions (CP) status, patient proximity to surfaces, and unit type likely influence MDRO contamination and bacterial bioburden levels on patient room surfaces. Identifying factors associated with environmental contamination in patient rooms and on shared unit surfaces could help identify important environmental MDRO transmission routes. Methods: Surfaces were sampled from MDRO CP and non-CP rooms, nursing stations, and mobile equipment in acute care, intensive care, and transplant units within 6 acute care hospitals using a convenience sampling approach blinded to cleaning events. Precaution rooms had patients with clinical or surveillance tests positive for methicillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci, carbapenem-resistant Enterobacteriaceae or Acinetobacter within the previous 6 months, or Clostridioides difficile toxin within the past 30 days. Rooms not meeting this definition were considered non-CP rooms. Samples were cultured for the above MDROs and total bioburden. Results: Overall, an estimated 13% of rooms were contaminated with at least 1 MDRO. MDROs were detected more frequently in CP rooms (32% of 209 room-sample events) than non-CP rooms (12% of 234 room-sample events). Surface bioburden did not differ significantly between CP and non-CP rooms or MDRO-positive and MDRO-negative rooms. Conclusions: CP room surfaces are contaminated more frequently than non-CP room surfaces; however, contamination of non-CP room surfaces is not uncommon and may be an important reservoir for ongoing MDRO transmission. MDRO contamination of non-CP rooms may indicate asymptomatic patient MDRO carriage, inadequate terminal cleaning, or cross-contamination of room surfaces via healthcare personnel hands. Abstract : We assessed the frequency of multidrug-resistant organism contamination on common area and patient contact and non-contact precautions room surfaces in 6 acute-care hospitals. Contamination was frequently detected in contact precautions rooms (32%) but was not uncommon in nonprecaution rooms (12%).